Experimental and clinical applications and outcomes of using different forms of suction in retrograde intrarenal surgery. Results from a systematic review - TANIDIR, YILÖREN (My University, 2023)
Objective: To identify the latest advances in suction devices and evaluate their effect in Retrograde intrarenal surgery (RIRS) and ureteroscopy for stones. Basic procedures: A systematic literature search was performed on 4th January 2023 using Scopus, PubMed, and EMBASE. Only English papers were included; both pediatric and adult studies were accepted. Duplicate studies, case reports, letters to the editor, and meeting abstracts were excluded. Main findings: Twenty-one papers were selected. Several methods have been proposed for suction use in RIRS, such as through the ureteral access sheath or directly to the scope. Artificial intelligence can also regulate this system, monitoring pressure and perfusion flow values. All the proposed techniques showed satisfactory perioperative results for operative time, stone-free rate (SFR), and residual fragments. Moreover, the reduction of intrarenal pressure (induced by aspiration) was also associated with a lower infection rate. Even the studies that considered kidney stones with a diameter of 20 mm or higher reported higher SFR and reduced postoperative complications. However, the lack of well-defined settings for suction pressure and fluid flow prevents the standardization of the procedure. Conclusion: Aspiration device in the surgical treatment of urinary stones favours a higher SFR, reducing infectious complications, as supported by the included studies. RIRS with a suction system provided to be a natural successor to the traditional technique, regulating intrarenal pressure and aspirating fine dust. © 2023 AEU. Published by Elsevier Espana, ˜ S.L.U. All rights reserved.

Objetivo: Identificar los últimos avances en los dispositivos de aspiración para la cirugía retrógrada intrarrenal (CRIR) y la ureteroscopia en el tratamiento de la litiasis, y evaluar los resultados de su aplicación. Procedimiento: El 4 de enero de 2023 se realizó una búsqueda bibliográfica sistemática en Scopus, PubMed y EMBASE. Sólo se incluyeron artículos en inglés; se aceptaron estudios en la población pediátrica y estudios en adultos. Se excluyeron los estudios duplicados, los informes de casos, las cartas al editor y los resúmenes de congresos. Hallazgos principales: Se seleccionaron 21 trabajos. Se han propuesto varios sistemas de aspiración para la CRIR: a través de la vaina de acceso ureteral o directamente por el endoscopio. La inteligencia artificial también puede desempenar ˜ un papel, monitorizando los valores de la presión y del flujo de irrigación. Todas las técnicas propuestas mostraron resultados perioperatorios satisfactorios en cuanto a tiempo quirúrgico, tasa libre de litiásis (TLL) y fragmentos residuales. Además, la reducción de la presión intrarrenal (mediante la aspiración) también se asoció a una tasa de infección menor. Incluso los estudios que incluyen cálculos renales con un diámetro de 20 mm o superior informan de una mayor TLL y una reducción de las complicaciones postoperatorias. Sin embargo, la falta de parámetros bien establecidos para la presión de la aspiración y el flujo de líquido impide la estandarización del procedimiento. Conclusión: Como ha sido demostrado en los estudios incluidos, el uso de dispositivos de aspiración en el tratamiento quirúrgico de los cálculos urinarios favorece la obtención de una TLL mayor y reduce las complicaciones infecciosas. La CRIR con sistema de aspiración podría sustituir a la técnica tradicional, gracias a sus ventajas asociadas al control de la presión intrarrenal y aspiración del polvo fino.
Aplicaciones clínicas, experimentales y resultados del uso de diferentes dispositivos de aspiración en la cirugía intrarrenal retrógrada. Revisión sistemática
Keywords: Cirugía intrarrenal retrógrada; Dispositivo de aspiración; Tasa libre de cálculos; Complicación infecciosa; Retrograde intrarenal surgery; Suction device; Stone-free rate; Infectious complication